CD4+ and CD8+ Tumor-Infiltrating Lymphocytes (TILs) Biomarkers: Role in Predicting the Stadium and Prognosis of Cervical Cancer - Humairah Medina Liza Lubis; Rafa Nabila Haifa; Rizky Yusfasari; Muhammad Zikri Agung Ramadhan (Indonesian Journal of Cancer, 2022)
Background: Tumor-infiltrating lymphocytes (TILs), mainly CD4+ and CD8 + T cells, have been extensively described in anti-tumor immunity, and knowledge of CD4+ and CD8+ T lymphocytes’ interplay in mediating the control of tumor growth exists. We use the role of TILs in predicting the prognosis of cervical cancer patients and develop the discovery of new immunotherapy strategies that specifically target TILs.Methods: A systematic review of studies carried out a histopathological and immunohistochemical examination of TILs and an immunotherapy treatment.Results: 10 articles were selected for a systematic review. Expression of TILs was associated with the progression of NIS to cervical cancer. CD4+ and CD8+ TILs can determine the stage and prognosis of cervical cancer. TILs immunotherapy is effective for all cervical cancer patients. Combination chemotherapy with anti-TILs immunotherapy and combination therapy for PD-1 and TILs was found to have a better potential for cervical cancer therapy.Conclusions: TILs can be a prognostic biomarker and a marker to predict cervical cancer.